(untitled) (Bulletin KNOB, 2002)
In last year’s Bulletin there was a discussion on the place of the ’large hall’ in the East-India House in Amsterdam drawn by Simon Fokke in 1771. On the basis of building-historical research carried out during the restoration in 1978, this hall must have been situated on the ground floor. It concerns the eastern room between the staircase and the former arsenal on the side of the courtyard. This room was two beam sections wide with two windows giving on to the courtyard. The large corbels, clearly depicted by Fokke, and the fireplace against the arsenal can only be situated there. In order to make the room look as large as possible, the draughtsman stood in the central space near the staircase, as it were. This way of drawing can also be demonstrated elsewhere. The only question remaining now is: was Simon Fokke’s company in the ’hall’ in question, which was the subject of the earlier discussion, or did he draw a room in this building after all? A kind of reception room may be thought of. However, this does not alter the fact that the back room on the ground floor occupied the most important place in the building then, because of its greater height.